The effects of zinc oxide non-eugenol and cellulose as periodontal dressings on open wounds after periodontal surgery - Yoeliani Budisidharta; Ahmad Syaify; Sri Pramestri Lastianny (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: Periodontal surgery forms a part of periodontal treatment that can sometimes cause open wounds, such as gingivectomy and depigmentation. Unfortunately, the healing process of open wounds can be inhibited due to bacterial infections and systemic factors. Thus, after surgery, the open wounds need to be closed with periodontal dressing. Purpose: This study aims to reveal the differences between using zinc oxide non-eugenol and cellulose periodontal dressings on open wounds after periodontal surgery. Methods: Thirty-two samples were divided into two groups. Group I consisted of 16 samples where zinc oxide non-eugenol was applied as a periodontal dressing. Similarly, Group II consisted of 16 samples where cellulose was applied as a periodontal dressing. The dressings were applied to open wounds after periodontal surgery using the split-mouth technique. Hence, zinc oxide non-eugenol was applied on the right side and cellulose was applied on the left side of the mouth. The patients’ healing index (HI) score was measured on day seven and their wound healing index (WHI) score was measured on days seven and twenty-one. Results: The day-seven HI score of the wounds applied with cellulose was higher than those applied with zinc oxide non-eugenol. Meanwhile, the WHI of the cellulose group was lower than that of the zinc oxide non-eugenol group, except on day twenty-one. Both the HI and WHI scores then were analysed using Mann Whitney. Conclusion: The application of cellulose is better than zinc oxide non-eugenol on the healing of open wounds after periodontal surgery.